A prospective study of epidemiology characteristics and outcomes of bloodstream infections in older patients. (10th November 2020) - Moschou, Aikaterini; Ioannou, Petros; Maraki, Sofia; Koutroumpakis, Filippos; Mamaloukaki, Maria; Bikis, Charalampos; Samonis, George; Papadakis, John A.; Kofteridis, Diamantis P.
Abstract: Objective: This study aimed to investigate the characteristics of bloodstream infections (BSIs) in older patients and describe the differences between community‐acquired, hospital‐acquired and health care–associated BSIs. Methods: A prospective observational study was conducted at the University Hospital of Heraklion, Crete, Greece. Epidemiology, clinical characteristics and outcomes of BSIs were recorded. Results: During a four‐year period, 113 BSIs were recorded. Of them, 42% occurred in male patients; patients' mean age was 80 years. BSIs were community‐acquired in 76% of patients, hospital‐acquired in 12% and health care–associated in 12%. The most commonly isolated bacteria were E coli and K pneumoniae . Thirty‐day mortality from detection of BSIs was 27%. Patients with fever, without septic shock and with appropriate empirical treatment were less likely to die. Conclusion: Community‐acquired, health care–associated and hospital‐acquired BSIs had different presentation, microbiology and outcomes. Older patients had a high mortality. The absence of fever, inappropriate empirical treatment and septic shock were independent mortality predictors.